2020
DOI: 10.1038/s41467-020-17067-x
|View full text |Cite
|
Sign up to set email alerts
|

Spermine synthase and MYC cooperate to maintain colorectal cancer cell survival by repressing Bim expression

Abstract: Dysregulation of polyamine metabolism has been linked to the development of colorectal cancer (CRC), but the underlying mechanism is incompletely characterized. Here, we report that spermine synthase (SMS), a polyamine biosynthetic enzyme, is overexpressed in CRC. Targeted disruption of SMS in CRC cells results in spermidine accumulation, which inhibits FOXO3a acetylation and allows subsequent translocation to the nucleus to transcriptionally induce expression of the proapoptotic protein Bim. However, this ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
46
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(46 citation statements)
references
References 66 publications
0
46
0
Order By: Relevance
“…A piece of strong evidence is that the levels of putrescine and agmatine were described to increase with the progression of CRC (38,39). Additionally, Guo et al found the synergistic effect of spermine synthase and oncogene MYC increased polyamine metabolites, suggesting dysregulation of polyamine metabolism has been linked to the development of CRC (40).…”
Section: Other Metabolites and Crcmentioning
confidence: 99%
“…A piece of strong evidence is that the levels of putrescine and agmatine were described to increase with the progression of CRC (38,39). Additionally, Guo et al found the synergistic effect of spermine synthase and oncogene MYC increased polyamine metabolites, suggesting dysregulation of polyamine metabolism has been linked to the development of CRC (40).…”
Section: Other Metabolites and Crcmentioning
confidence: 99%
“…In the future, an inhibitor suitable for clinical use could be developed for TXNRD1 and its combined use with sorafenib might improve the therapeutic effect. SMS, a polyamine biosynthetic enzyme, is overexpressed in patients with colorectal cancer and collaborates with MYC to promote colorectal cancer cell survival ( Guo et al, 2020 ). However, little is known about SMS in liver disease and HCC and more experiments are necessary to reveal its role in HCC.…”
Section: Discussionmentioning
confidence: 99%
“…In MCF-7 cell, oestrogen also positively regulates ODC1 gene expression and protein activity [ 7 ]. c-Myc on the other hand positively regulates ODC1 gene expression [ 36 , 37 ] and along with spermine synthase promotes cancer cell survival [ 38 ]. Thus, differences in gene expression patterns together with the hormone receptor status of the cells may contribute to their differential responses to polyamine pathway inhibition and may help predict the sensitivity of breast cancers to polyamine targeting therapy.…”
Section: Discussionmentioning
confidence: 99%